Study of some haematological and biochemical variables inchildren with iron- deficiency anaemia in Erbil-citv - A. Maulood, Kalthum (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was carried out in pediatric out patients ward of Rapareen hospital in Erbil city, which included 45 children with iron deficiency anaemia (IDA), males and females, whose age range is betweenl-5 years old, with 45 healthy children at same age and sex considerd as control group, to determine the hematological and biochemical variables. The results indicate a significant decrease (p < 0.01) in haemoglobin, packed cell volume and red blood cell count in children with iron deficiency aanemia (IDA) when compared with control. White blood cell count, lymphocyte number, platelet count and red distribution width were increased significantly (p < 0.01) in children with IDA when compared with control. No significant differences observed in neutrophil number in children with IDA and control. Mean corpuscular volume, mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration decreased significantly (p < 0.01) in children with IDA when compared with control. Significant decrease (p < 0.01) noticed in serum iron and transferrin saturation in children with IDA when compared with control. While total iron binding capacity increased significantly (p < 0.01) in children with IDA when compared with control. Serum creatinine, urea, aspartate transamminase and alanine